A two-stage treatment for Municipal Solid Waste Incineration (MSWI) bottom ash to remove agglomerated fine particles and leachable contaminants. (September 2017) - Alam, Qadeer; Florea, M.V.A.; Schollbach, K.; Brouwers, H.J.H.
Highlights: A two-stage treatment based on washing and sieving was developed for MSWI bottom ash. Fine particles (≤125 µm) rich in contaminants, were separated to achieve recyclable fractions of bottom ash. The leaching mechanisms of Cl −, SO4 2− and potentially toxic elements were studied. NaCl was identified as one of the soluble chloride species in the MSWI bottom ash. The majority of the Cl − and SO4 2− were found in the melt product around the particles. Abstract: In this lab study, a two-stage treatment was investigated to achieve the valorization of a municipal solid waste incineration (MSWI) bottom ash fraction below 4 mm. This fraction of MSWI bottom ash (BA) is the most contaminated one, containing potentially toxic elements (Cu, Cr, Mo and Sb), chlorides and sulfates. The BA was treated for recycling by separating agglomerated fine particles (≤125 µm) and soluble contaminants by using a sequence of sieving and washing. Initially, dry sieving was performed to obtain BA-S (≤125 µm), BA-M (0.125–1 mm) and BA-L (1–4 mm) fractions from the original sample. The complete separation of fine particles cannot be achieved by conventional sieving, because they are bound in a cementitious matrix around larger BA grains. Subsequently, a washing treatment was performed to enhance the liberation of the agglomerated fine particles from the BA-M and BA-L fractions. These fine particles were found to be similar to the particles of BA-S fraction in term of chemical composition. Furthermore, the leaching behavior of Cr, Mo Sb, chlorides and sulfates was investigated using various washing parameters. The proposed treatment for the separation of agglomerated fine particles with dry sieving and washing (L/S 3, 60 min) was successful in bringing the leaching of contaminants under the legal limit established by the Dutch environmental norms.